Increasing Productivity And Local Product Branding Optimization And Food Security in Desa Perkebunan Tanjung Kasau - Ismayadi; Zulfan; Putra Armidin, Ranu; Marpaung, T.J.; Satria Lubis, Andrew; Marpaung, J.L.; Gunaika, Raka; Qaedi Hutagalung, Arif; Hasan, Fuad; Rilani Manurung, Vindy; Syahputra Harahap, Edy (Talenta Publisher, 2023)
The need for fresh water fish consumption for the community is increasing, therefore the freshwater fishery business has very good business prospects to be developed in the form of both fresh and processed fish. A fish farming business must have implemented a planning function even though it is still simple, both in terms of technical preparation, equipment, labor, costs, implementation time and so on, even though it is not made in a structured manner. This service aims to improve the economy of the Tanjung Kasau Plantation Village through increasing the skills and knowledge of the community.